Science Process Skills of Madrasah Students and Implications for Science Learning in Islamic Education - Nurfika Putri Utami; Rahmi Susanti; Desi Desi (Yayasan Letiges Konsultan Sosial, 2026)
This study aimed to describe the profile of basic science process skills (SPS) among Grade XI students at MAN 3 Palembang and to analyze its implications for science learning in madrasahs within the context of Islamic education. The study employed a quantitative descriptive approach using a survey method involving 314 Grade XI students selected through total sampling. Data were collected using the Basic Process Skills Test (BAPS), consisting of 36 multiple-choice items, and were analyzed using descriptive statistics in the form of percentages. The results showed that students’ basic science process skills were generally at a moderate level, with an average achievement score of 65.89%. Among the six basic SPS aspects, prediction achieved the highest percentage (79.30%), followed by classification (73.51%), whereas measurement obtained the lowest percentage (50.11%). These findings indicate that students possess fundamental scientific thinking skills but still require reinforcement, particularly in measurement skills. In the context of Islamic education, the findings suggest the need for science learning in madrasahs to place greater emphasis on inquiry, laboratory activities, and scientific investigations integrated with Islamic values to develop students’ scientific competencies while fostering reflective and responsible individuals. This study provides diagnostic information regarding the strengths and weaknesses of each SPS aspect that can serve as a basis for developing learning strategies, assessment practices, and science curricula in madrasahs to support the improvement of science learning quality within Islamic education.